In Vitro toxicological effects of Fumonisin B1 and Beauvericin on bovine granulosa cells (International Journal of Health, Animal Science and Food Safety, 2015)
Fumonisin B1 (FB1) and beauvericin (BEA) are fusariotoxins found to co-exist in food and feed commodities. The aim of this study is to evaluate the individual and combined effects of FB1 and BEA on bovine granulosa cell proliferation and steroid production. Granulosa cells (GC) from small bovine follicles (1-5 mm) were cultured for 48 hours in 10% fetal bovine serum followed by 48 hours in a serum-free medium containing 500 ng/ml of testosterone (as an estradiol precursor), 30 ng/ml of FSH and 30 ng/ml of IGF-I with and without FB1 (3 µM) and BEA (3 µM). At the end of the experiment, the numbers of GC were determined using a Coulter counter (Beckman Coulter, USA) and concentrations of progesterone and estradiol in the culture medium were determined by radioimmunoassay. FB1 and BEA, both individually and in combination, showed an inhibitory effect (P < 0.05) on GC proliferation. The number of GC decreased by 17.7%, 54.2% and 61.0% after exposure to FB1 (3 µM), BEA (3 µM) and FB1 (3 µM) plus BEA (3 µM) respectively. FB1 (3 µM) had no effect (P > 0.05) on estradiol and progesterone production, whereas BEA (3 µM), both alone and in combination with FB1 (3 µM), was found to decrease (P < 0.001) the production of both steroids drastically. In conclusion, this in vitro study indicates that FB1 and BEA, both individually and in combination, may affect GC proliferation to different extents and shows the drastic inhibitory effects of BEA on steroid production.